2020
DOI: 10.1021/acsomega.0c00295
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Co–Mo-Supported Nano Alumina Ultradeep Hydrodesulfurization Catalyst for Production of Environmentally Friendly Diesel Fuel in a Trickle Bed Reactor

Abstract: In the present work, a nanocatalyst, γ-Al 2 O 3 nanoparticle-supported CoMo, was prepared experimentally and evaluated through a hydrodesulfurization (HDS) process for removing dibenzothiophene (DBT) from diesel fuel systematically in a trickle bed reactor (TBR). The results of the prepared catalyst characterization tests (scanning electron microscopy, X-ray diffraction (XRD), XRD phase quantification, and Brunner−Emmett−Teller) showed good distribution of active metals (CoMo), difference in surface morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It was found that running the HDS process at low diesel fuel space velocity promoted the DBT conversion on Co-Mo on gamma-alumina nanocatalyst in the HDS of diesel fuel. 67 For Fig. 5, it was observed that the increase of space velocity resulted in a signicant decrease in DBT conversion at all operating pressures and temperatures.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It was found that running the HDS process at low diesel fuel space velocity promoted the DBT conversion on Co-Mo on gamma-alumina nanocatalyst in the HDS of diesel fuel. 67 For Fig. 5, it was observed that the increase of space velocity resulted in a signicant decrease in DBT conversion at all operating pressures and temperatures.…”
Section: Resultsmentioning
confidence: 86%
“…[64][65][66] The FEME, XRD and BET analyses of the prepared catalyst were described elsewhere. 67 4.1.1 Inuence of reaction temperature on the conversion of DBT. For HDS reactions, it is well known that the operating temperature has a signicant impact on DBT conversion.…”
Section: Resultsmentioning
confidence: 99%
“…However, DFs obtained from gas condensates often do not meet modern standards not only in terms of the cetane number (CN), but also in terms of the content of sulfur compounds (SC). Traditionally, the reduction of the SC content in DFs in industry is carried out using hydrotreating processes [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%